How to design logos, symbols, and icons : 24 internationally renowned studios reveal how they develop trademarks for print and new media - Thomas, Gregory, 1949- (Cincinnati, Ohio : How Design, 2003)
"This book explores a broad range of design projects, strategies and creative processes. You'll see how marks were designed for banks and nonprofit organizations, feature films and churches ... for mergers, globalizations and diversifications. For each project, you'll get the whole story of how the logo, symbol or icon evolved smoothly (or not so smoothly) from the original concept, including: where ideas came from, whether they were instant inspirations or 2 A.M. breakthroughs; different directions that were considered; how initial roughs were influenced and shaped by the principles of good design and the realities of the client; and how the final design was adapted for use in various formats, from brochures and business cards to trucks and street banners."--Jacket.
Foreword / Earl Powell -- Introduction: 2,000 Words on 2,000 Years of Logos, Symbols and Icons -- The Art of the Mark: How to Design Successful Logos, Symbols and Icons -- The Ten Criteria for Development of a Successful Logo, Symbol or Icon -- The Three Categories of Logos, Symbols and Icons -- Flexible Identities -- Expo 2000 Hannover -- frog's New Identity -- Pittsburgh Children's Museum -- EMP -- Edmunds.com -- Logotypes -- Supersonic -- Two-Lane Media -- Netcenter -- Raymond Pirouz's Identity -- Audi -- Metreon--A Sony Entertainment Center -- ERAS Center -- Nike -- Symbolic/Indexic Marks -- Time Warner -- Chicago Orchestra Hall -- The Fashion Center, New York -- Banco Bradesco -- Equity Marketing -- The Presbyterian Church -- Los Angeles World Airports -- Detroit Edison -- e-business -- Conexant -- Bank of America -- Academic Investigations -- Texas Instruments -- The Los Angeles Philharmonic -- Logos on Screen -- Icon and Graphic Button Design.
Includes index.
Keywords: Trademarks -- Design; Logos (Symbols) -- Design